Intervención fisioterapéutica en niños nacidos pretérmino con retraso del neurodesarrollo. - Díaz Villagrán, Ivonne Aracely (2024)
Introduction: Neurodevelopment is a complex, continuous, and dynamic process that begins before birth and continues into adulthood and involves processes of growth, differentiation, and maturation of the nervous system. The term “neurodevelopmental delay” encompasses pathologies that hinder the chronological acquisition of motor, social, cognitive, and linguistic domains. Pediatric physiotherapy is in charge of the prevention, transformation, modification, and rehabilitation of alterations in motor development, and techniques are applied for the management of premature children in order to inhibit abnormal motor patterns that interfere in the correct development. Objective: To determine the benefits of physical therapy intervention in children with motor neurodevelopmental disorder antecedent to preterm birth through a literature review of randomised clinical trials. Methodology: The research was of the bibliographic type because scientific articles obtained from different high-impact databases were compiled; inclusion and exclusion criteria were applied for their selection. Results: Scientific articles were collected for evaluation by means of the PEDro scale (Physiotherapy Evidence Database), selecting those that obtained a score equal to or higher than 6. Finally, 25 articles were selected, which correspond to randomised clinical trials that were part of the study. Conclusion: Physiotherapeutic intervention in preterm infants is beneficial in several aspects of development and includes improving motor development and facilitating the acquisition of motor milestones.